Estudos sobre depressão na perspectiva da Psicologia Evolucionista - Tavares, Andreza Conceição de Souza (2023)
Depression is a health issue characterized by the presence of a depressed mood and a lack of interest in experiencing pleasure. In general, researchers have focused on studying depression with an emphasis on its symptoms and their consequences. However, evolutionary hypotheses assume that depression is related to problems that ultimately affect individuals' fitness. Therefore, solving these problems can alleviate depression. Fitness refers to the survival and reproduction of the species. Thus, the aim of this thesis is to foster the evolutionary discussion on depression. The first article provides an overview of the most prominent evolutionary hypotheses on depression. The results showed that there is no theoretical consensus in the literature, and the main discussion revolves around the adaptive or maladaptive function of depression. As a result, psychometric tools supporting these hypotheses were identified. Two of them were adapted in this thesis for the Brazilian population. The first assumes that depression is related to fitness. The second proposes that rumination in depression induces cognitive changes that lead to the analysis and solving of the problems related to the current depressive episode. Due to the common solving characteristic shared between the two hypotheses of the scales, the instruments were chosen for adaptation. Both showed good psychometric properties in the Brazilian population. However, measuring depression or its characteristics is not sufficient for its treatment. In this sense, the final paper of this thesis presents a group intervention protocol for depression based on cognitive-evolutionary therapy, which is grounded in the evolutionary perspective of human behavior and assumes that depression is related to fitness problems. Thus, in this thesis, the focus is directed towards the triggering problems of depression, demonstrating in the literature how these are related to fitness; discussing how humans typically solve their problems and the importance this process for human adaptability, survival and reproduction